Une illustration littéraire du mythe de l'Éternel Retour : « Le Jardin des supplices » d'Octave Mirbeau (1899) - Lair, Samuel (Studia Romanica Posnaniensia, 2008)
In Mirbeau's novel Le Jardin des supplices (1899), the circular representation, completed and relayed by design of the plant, should be read violently. The reader conceives some philosophical influences or convergences. The Narcissus myth is subjected here to a literary transmutation. The novel tells a personal obsession; it becomes a reconciliation between earlier fictions [L'Abbé Jules (1888), Dans le ciel (1892-1893)] and his dramatic work which is coming.